Nxopaxopo wa ndlela leyi vatlhokovetseri va vatsonga va paluxaka rifu hayona eka matsalwa ya Xitsonga lama nga hlawuriwa - Hlongwane, V. A. (University of Limpopo, 2014)
The main aim of this study is to analyse in detail different poems from different authors which reveal the way in which death comes to people and also explains how difficult it is, if someone has lost his/her lover. The first chapter reveals the general outline of the study, the problem statement, the aim, its significance and methodology. The most important terms of the study have been explained to be analysed. Chapter 2 explains defines and analysed the selected poems of different authors that reveal the ways in which death comes to living people. Chapter 3 deals with the general summary of this mini-dissertation. The recommendations for further research have been indicated in this chapter. Chapter 4 indicates a list of books which have been used in this mini-dissertation.
An analysis of the portrayal of death by vatsonga poets in the selected Xitsonga poetry texts
Thesis (M. A.) --University of Limpopo, 2014
Keywords: Tsonga poets; Portrayal of death; Death in literature; Poetry